Outcome of Buprenorphine maintenance treatment among Indian females with opioid dependence: Report from a tertiary addiction treatment center - Piyali Mandal; Atul Ambekar; Hemant Choudhary; Shubha Bagri (Indian Journal of Psychiatry)
Background: Buprenorphine maintenance treatment is an effective long-term treatment for opioid dependence. Indian experience with Buprenorphine-based treatment is more than 2 decades old now. No study has reported the outcome of maintenance treatment among Indian women with opioid dependence till date. Aims: The current study aims to assess the outcome of Buprenorphine maintenance among Indian females with opioid dependence. Material and Methods: Outpatient setting (specialty clinic for women) of a tertiary addiction treatment centre in India, Retrospective. Clinical record files of women who were initiated on buprenorphine maintenance treatment between 2015 and 2023 for opioid dependence were retrieved. Sociodemographic, clinical, and psychosocial data were extracted. Data analysis was conducted using SPSS version 26. Results: The median age of the sample was 43 years (31–52) (N = 43). The duration of maintenance treatment ranged from 1 to 175 months, with a median of 60 months (109–24) with around 75% of them following up during the time of data collection, self-reported abstinence in 88%, and negative urine drug screen in all the patients that were screened during the past year. Improvement documented in social (97.1%), family (92.3%), and occupational (91.7%) domains. Lapse on illicit opioid was recorded during the initial few weeks of treatment (27%, N = 37). Conclusions: This is the first study to demonstrate effectiveness of Buprenorphine maintenance treatment among Indian females with opioid dependence who have a distinct set of risk factors and a host of comorbidities along with several complications, making their care challenging for clinicians.